1989
DOI: 10.1001/jama.1989.03420140089033
|View full text |Cite
|
Sign up to set email alerts
|

β-Blockers and Primary Prevention of Coronary Heart Disease in Patients With High Blood Pressure

Abstract: We conducted a population-based, case-control study to determine whether beta-blockers, used for the treatment of hypertension, prevent first events of coronary heart disease. Cases were patients who had high blood pressure treated with medicines and who presented in 1982 to 1984 with angina or fatal or nonfatal myocardial infarction. Controls were a probability sample of health maintenance organization patients with pharmacologically treated hypertension and free of coronary heart disease. Blinded to case-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Atenolol (ATL), (RS)-2-{4-[2-hydroxy-3-(propan-2-ylamino) propoxy]phenyl} acetamide is a beta1-selective (cardio selective) beta-adrenergic receptor blocking agent without membrane stabilizing or intrinsic sympathomimetic (partial agonist) activities. This preferential effect is not absolute, however, and at higher doses, Atenolol inhibits beta2-adrenoreceptors, chiefly located in the bronchial and vascular musculature [10][11]. Losartan (LST), 2-butyl-4-chloro-1-{[2'-(1H-tetrazol-5-yl)biphenyl-4-yl]methyl}-1 H-imidazol-5-yl) methanol is an angiotensin II receptor (type AT1) antagonist.…”
Section: Introductionmentioning
confidence: 99%
“…Atenolol (ATL), (RS)-2-{4-[2-hydroxy-3-(propan-2-ylamino) propoxy]phenyl} acetamide is a beta1-selective (cardio selective) beta-adrenergic receptor blocking agent without membrane stabilizing or intrinsic sympathomimetic (partial agonist) activities. This preferential effect is not absolute, however, and at higher doses, Atenolol inhibits beta2-adrenoreceptors, chiefly located in the bronchial and vascular musculature [10][11]. Losartan (LST), 2-butyl-4-chloro-1-{[2'-(1H-tetrazol-5-yl)biphenyl-4-yl]methyl}-1 H-imidazol-5-yl) methanol is an angiotensin II receptor (type AT1) antagonist.…”
Section: Introductionmentioning
confidence: 99%
“…My first epidemiologic study was an observational case-control study of the association between anti-hypertensive drug use and the risk of coronary heart disease [4,5]. At the time, randomized trials that had evaluated high-dose diuretics against placebo in patients with hypertension showed reduced risks of major cardiovascular events [6].…”
mentioning
confidence: 99%
“…1 The other suggested that, compared with the use of high-dose diuretics, which is now no longer recommended, the use of ␤-blockers might be associated with a lower risk of coronary events in hypertensive patients. 2 While the news media's coverage of the risk study was transient, the pharmaceutical industry had a more sustained interest in the other publication.…”
mentioning
confidence: 99%